Theoretical transmissions for X-ray computed tomography studies of lithium-ion battery cathodes. (June 2020) - Heenan, T.M.M.; Tan, C.; Wade, A.J.; Jervis, R.; Brett, D.J.L.; Shearing, P.R.
Abstract: X-ray computed tomography (CT) has emerged as a powerful tool for the 3D characterisation of materials. However, in order to obtain a useful tomogram, sufficient image quality should be achieved in the radiographs before reconstruction into a 3D dataset. The ratio of signal- and contrast-to-noise (SNR and CNR, respectively) quantify the image quality and are largely determined by the transmission and detection of photons that have undergone useful interactions with the sample. Theoretical transmission can be predicted if only a few variables are known: the material chemistry and penetrating thickness e.g. the particle diameter. This work discusses the calculations required to obtain transmission values for various Li(NiX MnY CoZ )O2 (NMC) lithium-ion battery cathodes. These calculations produce reference plots for quick assessment of beam parameters when designing an experiment. This is then extended to the theoretical material thicknesses for optimum image contrast. Finally, the theoretically predicted transmission is validated through comparison to experimentally determined values. These calculations are not exclusive to NMC, nor battery materials, but may be applied as a framework to calculate various sample transmissions and therefore may aid in the design and characterisation of numerous materials. Graphical abstract: Unlabelled Image Highlights: A methodology for X-ray image optimisation has been outlined for battery materials. For optimal cathode image contrast 14% X-ray transmission should be targeted. Cathode thickness should be double the inverse of the attenuation coefficient. Deviations from theoretical predictions are outlined for real-world scenarios. To aid reader's future X-ray experiments a quick-reference guide is presented.